Analysis of CAMEL Components and Commercial Bank Performance: Panel Data Analysis - Ping, Kee Guek; Kusairi, Suhal (LPPM Universitas Terbuka, 2020)
The banking industry, one of the crucial elements in economic development, circulate funds from the surplus to the deficits to create a healthy, developing, and sustainable economic condition. Besides, the primary indicator of the soundness of the financial system is the performance of banking. Therefore, the objective of the study is to analyze Capital Adequacy, Asset Quality, Management Efficiency, Earning Quality, and Liquidity (CAMEL) towards bank performance. This study employed a static panel data model and utilized data of nine developed countries from 2013-2017. Findings. The study showed that capital adequacy and earning quality had a positive impact on bank performance and conversely asset quality,management efficiency, and liquidity has a negative effect on bank performance. Holding a high liquidity asset will reduce income as liquid assets are associated with lower rates of return. It will expect that higher liquidity will negatively affect bank performance. Therefore, the researcher can conclude that the banking industry should pay attention to CAMEL components for the maintenance and supervision of bank performance, and determinant factors are essential for sustainable economic growth.